Leadership as a Catalyst in Optimizing School Evaluation Implementation: An In-depth Study - Syahreza, Agung; Sukor, Radzuan (Development: Studies in Educational Management and Leadership, 2023)
This study aims to evaluate the implementation of top-tier Senior High Schools (SMU), focusing on the following aspects: the school's physical, social, and cultural environment, the student selection process for elite schools, the qualifications and recruitment of educational staff, the understanding and application of the curriculum, school management, and efforts to secure and utilize funds. It is an evaluative study that combines process and fidelity evaluation approaches, using ethnographic methods, conducted at SMAN 1 Semarang. Data was collected through observation, in-depth interviews, and documentation, analyzed using domain, taxonomy, componential, and theme analysis. The validity of the research data was checked with data source and method triangulation. The results show a conducive learning culture formed through the physical environment, a good and harmonious social and cultural school environment, a selective yet challenging recruitment process, curriculum development by increasing hours for subjects critical for college admission, limited but optimally utilized facilities, quality teaching and learning processes, good, communicative, and transparent school management, and funding supported by routine fees and voluntary donations from stakeholders. Despite the non-formal designation of "elite" schools, community recognition is naturally given based on the school's educational implementation and services.